2018
DOI: 10.1093/nar/gky1007
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification and METTL3 modulate enterovirus 71 replication

Abstract: N 6-methyladenosine (m6A) constitutes one of the most abundant internal RNA modifications and is critical for RNA metabolism and function. It has been previously reported that viral RNA contains internal m6A modifications; however, only recently the function of m6A modification in viral RNAs has been elucidated during infections of HIV, hepatitis C virus and Zika virus. In the present study, we found that enterovirus 71 (EV71) RNA undergoes m6A modification during viral infection, which alters the expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
204
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(211 citation statements)
references
References 56 publications
(54 reference statements)
7
204
0
Order By: Relevance
“…METTL3 facilitates the stability of viral RNAdependent RNA polymerase 3D and boosts type 71 enterovirus replication by inducing sumoylation and ubiquitination of the polymerase [53].…”
Section: Mettl3mentioning
confidence: 99%
“…METTL3 facilitates the stability of viral RNAdependent RNA polymerase 3D and boosts type 71 enterovirus replication by inducing sumoylation and ubiquitination of the polymerase [53].…”
Section: Mettl3mentioning
confidence: 99%
“…Although the mechanism remains uncertain, one assumption is that YTHDF2 promotes the degradation of antiviral gene transcripts [62]. Third, m 6 A modifications play a positive role in enterovirus 71 (EV71) replication [63]. Fourth, m 6 A modifications impair viral replication by blocking the packaging of viral RNA into new virions during flavivirus infections [64].…”
Section: Rna M 6 a Modifications And Viral Infectionmentioning
confidence: 99%
“…Previously, we reported that m 6 A residues enhance viral gene expression and replication for HIV-1, influenza A virus and the polyoma virus SV40 (911) and others have also reported that m 6 A residues promote HIV-1 and enterovirus 71 replication (12, 13) and play a role in the activation of lytic replication in Kaposi’s sarcoma herpesvirus (KSHV)-infected cells (14, 15). More recently, we reported that addition of m 5 C also enhances HIV-1 gene expression (8), and others have reported that Nm modifications on HIV-1 transcripts promote HIV-1 replication by inhibiting the detection of viral transcripts by the innate antiviral RNA sensor MDA5 (16).…”
Section: Introductionmentioning
confidence: 98%